IN VITRO EVALUATION OF SUGARCANE TOPS BASED COMPLETE FEED - R. Prabakaran; M. Ramachandran; K. Ayyappan; V. Sasikala (Indian Journal of Veterinary and Animal Sciences Research, 2026)
The present research work was carried out to evaluate the effect of inclusion of different levels of sugarcane tops and different levels of crude protein in the complete feed on in vitro parameters. Three complete feeds were prepared with three different crude protein levels of 8%, 10% and 12% utilizing sorghum stover as a roughage source. Twelve sugarcane tops based complete feeds were prepared by replacing sorghum stover with sugarcane tops at four different levels of 25%, 50%, 75% and 100%, with three different crude protein levels (8%, 10% and 12%) in each level of inclusion. Total digestible nutrients of 50% and roughage:concentrate ratio of 65:35 have been maintained in all the fifteen complete feeds (CFE 1 to CFE 15). There was a significant difference (P0.05) among complete feeds. In vitro organic matter degradability (%) was significantly higher (P